The scientists. George Istomin (to the 80-th anniversary of birthday) - Golka, Grigoriy; Bitchuyk, Dmytro; Fadeyev, Oleg; Oleynik, Oleksandr; Istomin, Dmytro (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
The article is devoted to the 80 anniversary from the birthday of doctor of medical Sciences Professor Grigoriy P. Istomin.